Analysis of Local Wisdom Integration with Environmental Law In Nagari Pariangan Tanah Datar District, West Sumatra - Wahyuni, Sri; Susanti, Heni (Universitas Ekasakti, 2023)
The local wisdom of the Indonesian people can be the basis for the concept of sustainable development. However, the challenge is that the complexity of legal rules can cause clashes in the context of the relationship between the right to control the state and the local wisdom values ​​that live and grow in the Nagari Pariangan community, Tanah Datar Regency, West Sumatra. This condition needs to be studied to find an appropriate legal construction that is integrated with the social system. This research aims to identify local wisdom values ​​with an environmental legal perspective possessed by the people of Nagari Pariangan. Examining and describing customary institutions in Nagari Pariangan in integrating customary norms with environmental law. This research used a qualitative approach with descriptive methods, which aimed to analyze and describe the integration of environmental law with local wisdom values. The subjects of this research were the Nagari Traditional Leaders, the Nagari Government, Tuangku Nagari and the local community. Research data collection used observational methods, focus group discussions, interviews and documentation from various sources that were related and support data analysis using data reduction, data presentation and drawing conclusions. The results of the research showed that, 1) The local wisdom values ​​of Nagari Pariangan as guidelines for community life in protecting the environment are manifested in customary norms that natural resources in the form of land/fields/rice fields, forests and rivers cannot belong to individuals but rather belong to groups/groups. traditional tribes and their management must obtain approval from Ninik Mamak; 2) The Tigo Tungku Sajarangan government integrates Nagari Pariangan traditional norms with environmental law which is realized in consensus deliberation between Ninik Mamak in every development plan launched by the Nagari Government, Regency, Provincial and Central Governments. If the results of the consensus deliberation are unanimous then it becomes the final decision made by each of the children/nephews/community, which supports the integration of environmental law with customary law and local wisdom.